No time to waste: necessary health support for retired professional rugby players - Gouttebarge, V.; Janse van Rensburg, C.; Kerkhoffs, G. (South African Journal of Sports Medicine, 2021)
There has been increasing scrutiny of professional rugby following the concern that retired players might face several negative health conditions. Currently, support measures addressing the health of retired professional rugby players are not systematically implemented. This is unusual as professional rugby stakeholders have the duty of care to protect and promote the long-term health of retired players. Professional football has a health programme for retired players that is implemented globally. This programme formed the basis for the After Rugby Career Consultation (ARCC) which was developed to empower the sustainable health and quality of life of retired professional rugby players. The ARCC relies on information from three sources: (1) educational material, (2) medical examination, and (3) guidance, referral and/or monitoring. The South African rugby stakeholders have connected to pilot the ARCC as there is no time to waste: a step towards necessary health support for retired professional rugby players is needed.